Surface Characterization Techniques: A Systematic Review of their Principles, Applications, and Perspectives in Corrosion Studies. Issue 11 (1st November 2022) - Fanijo, Ebenezer O.; Thomas, Joseph G.; Zhu, Yizheng; Cai, Wenjun; Brand, Alexander S.
Abstract : The nanoscale quantification of the electrochemical behavior in metals is critical to understanding the microstructure-corrosion relationship and subsequently controlling it. In this article, the application of advanced surface characterization techniques—atomic force microscopy (AFM), vertical scanning interferometry (VSI), digital holography microscopy (DHM), and other quantitative phase microscopy (QPM) techniques—for surface corrosion monitoring in metals at the micro- and nanoscale are systematically reviewed and discussed in detail. Interestingly in situ, real-time nanoscale topography evolution that enables measurement of time-dependent local dissolution rate as often tracked from numerical construction of QPM is also presented. This study demonstrates the considerable attributes of correlative advanced techniques for identifying nanoscale corrosion mechanisms, enabling the informed development of next-generation inhibition technologies, and improving corrosion predictive models.